Carpal Tunnel Syndrome and its relation to dentist - Anggayanti, Nyoman Ayu; Adiatmika, I Putu Gde (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2015)
Introduction: Carpal Tunnel Syndrome (CTS) is a compressive neuropathy, caused by mechanical distortion produced by a compressive force of the median nerve at the level of the wrist. Primary sign is pain in the wrist, tingling sensation, pain or numbness in thumb, index finger, middle finger, and radial side of the ring finger, also there is a reduction of the grip strength and function of the affected hand. This sign tend to be worse at night and clumsiness during the activities that requiring wrist flexion. This syndrome is well-known and frequent accounts for 90% of all entrapment neuropathies. Incidence rates up to 276:100.000 per year. More common in females than in males, its occurrence is commonly bilaterally with a peak age range of 40 to 60 years. This is the productive age, which is often reported that the Carpal Tunnel Syndrome are work-related musculoskeletal disorders caused by strain and repeated movements. Disscussion: Dentist are high risks to go through musculoskeletal disorders covering wrist joint. The condition may happen because of the dentist position while handling patients is not in ergonomic position. These include repetitive prolonged hand activities, forceful static posture of wrist, vibration, and localized mechanical stress. To reduce the symptoms of musculoskeletal disorders since the beginning, has developed an integrated concept of teamwork in a modern dental practice. This concept is known as the four-handed dentistry which consists of dentists and assistants with their respective skills. Conclusion: The four-handed treatment techniques has been developed that is now largely acceptable. The concept of four-handed dentistry is expected to prevent the movement that makes the muscles tense, especially in the area around the wrist. And may ultimately reduce the incidence of Carpal Tunnel Syndrome